2022
DOI: 10.3389/fgene.2021.769849
|View full text |Cite
|
Sign up to set email alerts
|

A Random Regression Model Based on a Single-Step Method for Improving the Genomic Prediction Accuracy of Residual Feed Intake in Pigs

Abstract: Residual feed intake (RFI) is considered as a measurement of feed efficiency, which is greatly related to the growth performance in pigs. Daily feeding records can be obtained from automatic feeders. In general, RFI is usually calculated from the total measurement records during the whole test period. This measurement cannot reflect genetic changes in different growth periods during the test. A random regression model (RRM) provides a method to model such type of longitudinal data. To improve the accuracy of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…These results corroborate with Wang et al. (2022), who reported that models using LP of higher order were also better for genomic prediction of feed efficiency in pigs. The models that assumed heterogeneous residual variance also showed better goodness of fit, suggesting considerable changes in the residual variance over the feedlot period.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…These results corroborate with Wang et al. (2022), who reported that models using LP of higher order were also better for genomic prediction of feed efficiency in pigs. The models that assumed heterogeneous residual variance also showed better goodness of fit, suggesting considerable changes in the residual variance over the feedlot period.…”
Section: Discussionsupporting
confidence: 92%
“…In contrast, Wang et al. (2022) related higher heritability estimates, ranging from 0.11 to 0.48, in a pig population using an RRM based on LPs.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations